STUDI TATA LETAK GUDANG DALAM PENGARUHNYA TERHADAP PRODUKTIVITAS KERJA DI CV IMEXINDO NUSANTARA - Eka Rahmawati; Henry Yuliamir; Yuniarto Rahmat Satato; Hendrajaya; Hendrajaya Hendrajaya (Bajang Institute, 2025)
Because the warehouse serves as a location to keep goods that the business will deliver to clients, the goal of this study is to ascertain the extent to which the layout of the warehouse affects the manufacturing process. The warehouse is crucial to the efficient operation of the value-added process in addition to being a key component of the supply chain and logistics system overall. The results of this study, which used a quantitative research methodology, showed a significant relationship between job productivity and warehouse layout. 75 respondents from warehouse employees were involved in this study